The Liberation of Lithuania in the West under détente, 1970–1974 - Banionis, Juozas (Genocidas ir rezistencija, 2004)
During the period when international tension between East and West began to reduce, that is, the period of détente, the organizations involved in advocating the liberation of Lithuania, the Lithuanian American Council (ALT), the Supreme Committee for the Liberation of Lithuania (VLIK) and the Lithuanian World Community (PLB) had to restructure their political activities.Having embarked on its fourth decade of liberation activities, the ALT continued to adhere to its anti-Communist course and encouraged publication of the USSR's crimes against Lithuania. This was realized through moulding a positive opinion in American society and the U.S. administration towards Lithuania's case for freedom, by promoting the history of the Lithuanian nation, and working for the unity of the organizations involved in the cause of liberation. A good example of this was the exhibition on genocide of the Lithuanian nation, organized in Chicago on 13–20 June 1970, which exposed the real face of Soviet practice, under wise leadership and encouraged by optimistic signs of the struggle for freedom from within the occupied homeland. VLIK resisted the attacks of Soviet propaganda and started strengthening its liberation activities. With this intention, they reformed the board and established closer liaison with the western Lithuanians émigrés, the so-called "free Lithuanians".
Keywords: Soviet occupation; emigree; emigree organisation; USA; Lithuanian liberation movement